Analisis Kestabilan Global Model Epidemik SIRS menggunakan Fungsi Lyapunov - Yuni Yulida; Faisal Faisal; Muhammad Ahsar Karim (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
This paper presents the SIRS epidemic model. Furthermore, the model is investigated the existence of the equilibrium point, and the global stability of the equilibrium point using the function Lyapunov.